2018
DOI: 10.1159/000488827
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Plays a Protective Role in Iodinated Contrast-Induced Acute Renal Tubular Epithelial Cells Injury

Abstract: Background/Aims: Contrast induced-acute kidney injury (CI-AKI) is one of the most common causes of acute kidney injury (AKI) in hospitalized patients. Mitophagy, the selective elimination of mitochondria via autophagy, is an important mechanism of mitochondrial quality control in physiological and pathological conditions. In this study, we aimed to determine effects of iohexol and iodixanol on mitochondrial reactive oxygen species (ROS), mitophagy and the potential role of mitophagy in CI-AKI cell models. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 43 publications
(41 reference statements)
5
50
0
Order By: Relevance
“…Since oxidative stress is closely related with mitophagy [24], and mitophagy protects cells from apoptosis under environmental stress [25, 26]. We next explore whether high glucose inhibits RPE proliferation and promotes cell apoptosis by regulating oxidative stress mediated mitophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Since oxidative stress is closely related with mitophagy [24], and mitophagy protects cells from apoptosis under environmental stress [25, 26]. We next explore whether high glucose inhibits RPE proliferation and promotes cell apoptosis by regulating oxidative stress mediated mitophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Blotting. Cells or renal cortical tissues (n = 3 from each group) were isolated, as described previously [6,7]. Nuclear and cytoplasm protein were extracted according to the operating instructions.…”
Section: Westernmentioning
confidence: 99%
“…Determination of Reactive Oxygen Species. Mitochondrial ROS in HK-2 cells was evaluated by using MitoSOX Red (Invitrogen Corporation, USA) as previously described [7], according to the manufacturer's instruction. Briefly, cells growing in cell culture plates were rinsed and incubated in MitoSOX (Invitrogen Corporation, USA) for 8 minutes at 37°C in the dark.…”
Section: Westernmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many researchers have shown the protective role of mitophagy in oxidative stress, mitochondrial dysfunction, and apoptosis [56,57], the regulation of mitophagy in an ethanol environment is still controversial. We found that ethanol-activated caspase-1 plays a key role in parkin-mediated mitophagy and neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%